REVIEW AND PROFILE OF PRACTICING THE LONG TERM IN RACE SERGIPE (Fiep Bulletin - online, 2011)
This work is a descriptive study of prevalence. It is the objective of this study to gather information and describe the profile of the practitioners of long runs in the state of Sergipe. In recent decades with the disclosure about the importance of regular physical activity linked to improved health levels associated with lower rates of morbidity and mortality, has shown an increase in the number of supporters within the general population. The occurrence of this fact led the population to change their habits, knowledge about the benefits of physical activity and in some cases adopting a more active lifestyle. The sample consisted of 95 subjects who used the race as a long-term fitness and competitive non-competitive, and who kept a regular attendance of training in this modality and a recurrent periodicity in major endurance races that exist in Sergipe. It may be noted that with regard to the recall of the symptoms of injury prevalence in 2009 reached a high rate among pedestrians, 65% of individuals in the sample stated that they felt some discomfort that hindered or stopped their normal activities in training and competitions, the direct causes of the symptoms caused by the installation of the mechanisms of injury. Observers can be a high number of individuals develop the practice of racing with signs of bruising and sprains, which may aggravate the injury, and cause temporary or definitive withdrawal of physical activity and exercise.
Keywords: physical activity; quality of life; injuries